Recombinant human growth hormone treatment of Floating-Harbor syndrome: a case report and literature review - Qing He; Yi Deng; Lei Xu; Zhe Xu; Yi Ding; Menghui Wu (BMC Pediatrics)
Abstract Background Floating Harbor syndrome (FHS) is a rare genetic disorder with over 100 reported cases worldwide and less than 30 treated with recombinant human growth hormone (rhGH). This article reports the clinical characteristics of a child with FHS and the effect of rhGH on height increase. Case summary The patient in this case exhibits the most typical features of FHS. Whole exome sequencing (WES) detected a pathogenic variant (c.7303 C > T, p.R2435X) in the SRCAP gene of this patient, which is a denovo variant. Has good sensitivity to rhGH treatment. The literature review included 28 children who received rhGH treatment, most of whom showed an increase in height SDS without any adverse reactions. Conclusion For patients with characteristic clinical manifestations, the diagnosis of FHS should be considered, and further pathogenic gene sequencing analysis should be performed to assist in the diagnosis. The genetic characteristic is a heterozygous nonsense mutation of the SRCAP gene. rhGH treatment is an effective treatment method for FHS.